Verbal strategies for delivering bad news in oncology settings: a discourse-pragmatic approach - Agus Setyo Nugroho (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Cancer disclosure in oncology settings presents profound communicative challenges, as physicians must convey life-altering information while preserving patient dignity, trust, and emotional stability. Objective: This study aims to examine the sequential organization, politeness strategies, and discursive framing mechanisms employed by oncologists when delivering serious diagnoses and poor prognoses. Method: Using a qualitative multi-method design, this research analyzes 32 recorded oncology consultations, 12 physician interviews, and institutional communication guidelines through Conversation Analysis, politeness theory, and discourse-pragmatic framing analysis. Results: The findings reveal a recurrent sequential structure comprising preparatory pre-sequences, mitigated disclosure, strategic pauses, empathic alignment, and prognostic reframing. Politeness strategies such as hedging, inclusive pronouns, and euphemistic substitution systematically mitigate face-threatening acts while maintaining epistemic authority. Discursive framing shifts emphasis from biomedical finality to quality-of-life orientation and therapeutic continuity, balancing realism and hope. Implication: These findings suggest that effective cancer disclosure requires integrating sequential, relational, and framing strategies to balance medical clarity with emotional support, thereby enhancing patient trust and ethical communication in oncology. Novelty: The novelty of this study lies in integrating sequential, relational, and framing dimensions into a unified discourse-pragmatic model, offering both theoretical refinement and practical implications for ethically responsible communication in oncology.